Numerical simulation of keyhole behaviors and fluid dynamics in laser–gas metal arc hybrid welding of ferrite stainless steel plates. (January 2017) - Wu, C.S.; Zhang, H.T.; Chen, J.
Graphical abstract: The weld pool, keyhole, and fluid flow field in laser–GMAW hybrid welding. Highlights: A 3D transient model is developed to analyze the keyhole dynamics and weld pool behaviors in laser–GMAW hybrid welding. The droplets transfer and interaction of laser/arc are taken into account. The phenomena of keyhole channel closing and reopening momentarily is predicted. The impingement of droplets on the weld pool and the fluctuation of weld pool surface are depicted. The predicted weld bead shape and fusion line match well with the experimentally measured ones. Abstract: The fluid dynamics in weld pool and keyhole behaviors in laser–gas metal arc hybrid welding play a dominant role in affecting the weld quality of ferrite stainless steel plates. In this study, a transient model is developed for numerical simulation of the keyhole dynamics and heat transfer & fluid flow in hybrid weld pool. The heat, mass and momentum transfer due to droplets as well as the interaction between laser and arc are taken into account. The formation, expansion and sustainment of keyhole in weld pool are numerically simulated, and the transient variation of keyhole is demonstrated in three stages. The weld pool and keyhole shapes and sizes, and the fluid flow and thermal field in hybrid weld pool are quantitatively analyzed. The model is validated by hybrid welding experiments on ferrite stainless steel plates. It lays foundation for optimizing the process parameters in hybrid welding.